2021
DOI: 10.1109/access.2021.3093113
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Differential Crossover and Quantum Particle Swarm Optimization for IoT Applications

Abstract: An optimized design with real-time and multiple realistic constraints in complex engineering systems is a crucial challenge for designers. In the non-uniform Internet of Things (IoT) node deployments, the approximation accuracy is directly affected by the parameters like node density and coverage. We propose a novel enhanced differential crossover quantum particle swarm optimization algorithm for solving nonlinear numerical problems. The algorithm is based on hybrid optimization using quantum PSO. Differential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(14 citation statements)
references
References 49 publications
0
14
0
Order By: Relevance
“…Niwa et al in [ 5 ] constructed a simulation to investigate the effect of the quantum error-correcting code in five-qubit codes, seven-qubit codes, and nine-qubit codes and their fault tolerance operations when the error correction process produces an error. This study showed that the seven-qubit code scheme is the most effective in [ 4 – 10 ] or less of decoherent rate and when the standard operational error is 10–3 or less. In addition, the error correction process in the seven-qubit code is operated at every 50 to 200 main gates even though there is that both errors exist.…”
Section: Related Workmentioning
confidence: 92%
“…Niwa et al in [ 5 ] constructed a simulation to investigate the effect of the quantum error-correcting code in five-qubit codes, seven-qubit codes, and nine-qubit codes and their fault tolerance operations when the error correction process produces an error. This study showed that the seven-qubit code scheme is the most effective in [ 4 – 10 ] or less of decoherent rate and when the standard operational error is 10–3 or less. In addition, the error correction process in the seven-qubit code is operated at every 50 to 200 main gates even though there is that both errors exist.…”
Section: Related Workmentioning
confidence: 92%
“…In addition, a concept of iteration division, shown in Algorithm 2, is employed to reach a balanced diversification and intensification process. For the first number of iterations 𝑡𝑡 𝑣𝑣 , the range of velocity [𝑣𝑣 𝑚𝑚𝑖𝑖𝑛𝑛 , 𝑣𝑣 𝑚𝑚𝑎𝑎𝑚𝑚 ] is selected using the equation (39) with 𝑘𝑘 𝑏𝑏 = 1 (𝑡𝑡 < 𝑡𝑡 𝑣𝑣 ) and for the rest of the iterations with 𝑘𝑘 𝑏𝑏 ∈ (0,1) (𝑡𝑡 > 𝑡𝑡 𝑣𝑣 ). k is a constant called the decreasing velocity coefficient and belongs to the interval (0,1) [23].…”
Section: B the Dynamic Parameter And Velocity Controllermentioning
confidence: 99%
“…A dynamic inertia weight strategy is integrated into the proposed algorithm, where the value of w is linearly decreased from 𝑤𝑤 𝑚𝑚𝑎𝑎𝑚𝑚 (initial value) to 𝑤𝑤 𝑚𝑚𝑖𝑖𝑛𝑛 (final value) according to equation (39), where 𝑟𝑟 is the damping coefficient selected within the interval (0,1]. With this strategy, the tendency of particles to global search is decreased continuously, and at the same time, their tendency to local search increases continuously.…”
Section: B the Dynamic Parameter And Velocity Controllermentioning
confidence: 99%
“…An enhanced ultrasound-based time of arrival technique [21] permits calculating the position in three dimensions and provides the data orientation. Cricket, a ToA-based localization approach [22], uses ultrasound transmitters with known locations. The anchor node evaluates the location of the unknown node with high accuracy.…”
Section: Time Of Arrivalmentioning
confidence: 99%